Sustainable Fisheries and Community Nutrition Improvement - Rafi Ahmad; Nadia El-Masry (Journal of Community Action, 2026)
This study examines the relationship between sustainable fisheries and community nutrition improvement using a systematic literature review approach. The analysis integrates findings from peer-reviewed studies, policy reports, and empirical research on fisheries management, marine ecosystems, and nutritional outcomes. A total of 19 selected references were analyzed using thematic synthesis across ecological, socioeconomic, and nutritional dimensions. Results show that sustainable fisheries management, particularly through marine protected areas, can increase fish biomass by up to 15 percent and fish catch by up to 20 percent. These ecological improvements directly enhance food availability in coastal communities. Fisheries also contribute to poverty reduction by providing stable livelihoods and income sources, which improve household food security. In addition, fish consumption significantly enhances dietary diversity and micronutrient intake, especially in vulnerable populations. However, challenges remain in distribution systems, where export-oriented supply chains limit local access to nutritious fish. Community-based innovations such as small-scale aquaculture and fish processing technologies improve food access and reduce post-harvest losses. The study concludes that sustainable fisheries function as an integrated system linking ecosystem health, economic stability, and human nutrition. Policy integration between fisheries management and public health is essential to maximize nutritional benefits and ensure equitable food access in coastal regions.